LAT, EGFR -pY197, PCNL2, CDX2, HLA-DPDQDR, bromodeoxyuridine, JAM-A, and ezrin immunoreactants in a rubbed spongiotic dermatitis - Ana Maria Abreu Velez; A. Deo Klein; Michael S. Howard (Our Dermatology Online, 2011)
Background: Acute and subacute spongiotic dermatitides are among the most commonly diagnosed types of dermatitis. Many patients rub their lesions, with the lesions becoming clinically thickened. The precise immunologic mechanisms within the thickening process are not well defined. Case report: An 85 year old male presented with the sudden clinical appearance of erythematous patches and small blisters on the back of his legs, with pruritis. Methods: Skin biopsies, one from a rubbed lesion and one from a non-rubbed lesion were submitted for hematoxylin and eosin (H&E), immunohistochemistry (IHC), and for direct immunofluorescence (DIF) analysis. Results: The H&E staining demonstrated classic features of a spongiotic dermatitis, but in the rubbed areas psoriasiform hyperplasia was also seen. The psoriasiform areas demonstrated positive, focal IHC staining with bromodeoxyuridine, LAT, EGFR-pY197, PCNL2, CDX2, and HLA-DPDQDR antibodies. DIF staining revealed positive staining of JAM-A and ezrin in the non-rubbed specimens in both the spongiotic epidermis and in the adjacent vessels; normal expression of these markers was appreciated in the rubbed biopsy. Conclusions: The immune response seems to be complex when a spongiotic dermatitis is converted from a non-rubbed to a rubbed lesion with histologic features of psoriasiform hyperplasia.